KONSEP DIVERSI DALAM PERSPEKTIF APARAT PENEGAK HUKUM DI KABUPATEN PELALAWAN - Yuni Angraini; Dessy Artina; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, Diversion is an important part in the implementation of Juvenile Criminal Justice. Diversion is an action or treatment to divert a case from a formal process to an informal process, or to place the perpetrators of child crimes out of the juvenile justice system. This means that not all cases of juvenile delinquents must be resolved through formal courts, and provide an alternative for settlement with a justice approach in the best interests of the child and by considering justice for the victim.However, in Pelalawan Regency there are still many cases of crimes committed by children which end in criminal decisions at the Pelalawan District Court. The purpose of writing this thesis, namely: First, to determine the perception of law enforcement officers in Pelalawan Regency related to the concept of diversion. Second, to find out the obstacles to the implementation of diversion by law enforcement officers in Pelalawan Regency.This type of research can be classified in the type of sociological juridical research, because in this study the author directly conducts research in the place under study in order to provide a complete and clear picture of the problem to be studied, while the population and sample are all parties related to the problem studied in this study, data sources used, primary data, secondary data and tertiary data, data collection techniques in this study with interviews and library data.From the results of this study it was concluded, first, the perception of law enforcement officers in the implementation of diversion is very important in fighting for the rights of child offenders and carrying out in accordance with applicable regulations, the role of law enforcement officers in carrying out diversion which is the transfer of settlement of child cases from the criminal justice process to The process outside the criminal court according to the researcher is not carried out properly because there are still many law enforcement officers, especially child investigators who understand the Juvenile Criminal Justice System. As well as the lack of certification by law enforcement officers in handling cases of children in conflict with the law. This can be seen from the number of child cases that end in criminal decisions in court. Second, the obstacles in implementing Diversion in Pelalawan Regency, namely at the stage of investigation, prosecution, courts that come from the victims themselves who do not want to make peace with child perpetrators, and the lack of certification and efforts of investigators in facilitating diversion.Keywords: Diversion – Perspective - Law Enforcement Apparatus